Peningkatan Kreativitas dan Prestasi Belajar Sejarah Dengan Materi Kolonialisme dan Imperealisme Melalui Model Pembelajaran Project-Based Learning - Slamet Dwi Nugroho (Center for Research and Community Service (LPPM) University of Abulyatama, 2020)
Quality education emphasis on the important learning process for students; Meaningful learning is not only evident from the high scores achieved by students. However, also the learning process can instil and foster the student's character, such as a creative attitude that will deliver a brilliant student achievement. In this study aims to analyze the increase in creativity and student learning outcomes by using a project-based learning model. This research was conducted at Public High School 1 Piyungan Yogyakarta with a sample size of 34 students of class XI IPS on the topics of Colonialism and Imperialism. This research included in this type of classroom action research whose implementation consists of two cycles I,e cycle 1 and cycle 2. Data collection technique used observation, questionnaires and learning achievement test instruments. While the data analysis technique uses the percentage of mastery learning outcomes, classically results show that there is an increase in learning achievement and creativity of the students at each cycle. It explains that the model of Project-Based Learning can increase creativity and student achievement.